(untitled) (Bangladesh Journal of Medical Science, 2019)
Background & Objective: The aim of present study was to evaluate herbal analgesic cream containing Nigella sativa oil as an active ingredient, standardization of Nigella sativa oil and evaluation of irritation/sensitization potential of formulation. Material & Method: For this, HPLC analysis of oil, skin irritation test on rabbits and patch testing on human skin was conducted. HPLC analysis using C-18 column, using an isocratic mobile phase of water: methanol (10:90) at flow rate of 1 ml/inactive ingredient: thymoquinone purified from the oil was found to be 1.42g (28.4 %). Safety assessment of analgesic cream was based on Primary Dermal Irritation Index (PDII) by Draize method. Result: According to Draize standard scoring system of reactions PDII was found 0.04 which comes under the category of non irritant. Patch testing on human volunteers revealed that none of volunteers showed any sign of skin reactions. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.163-168